Potential of Creative Economic Financing Innovation in The Madura Area Based on Village Sharia Investment System as East Java's New Economic Support - Palani, Herman; -, Handoko (Jurnal Ilmu Ekonomi Terapan, 2018)
Poverty and human development are big problems in the Madura region. The HDI of the four districts in the region is the lowest in East Java, and more than 21.46% of the population lives in poverty. On the other hand, the potential of the creative economy in this area is very potential, such as tourism development, agriculture, crafts, culinary, and performing arts. However, limited access to finance for business development makes the development of the creative economy slow. Therefore, innovation is needed, especially in terms of financing to support the economy in this region. Optimization of BUMDes with a sharia investment system (Village Sharia Investment System) is a new financing solution for the community and has the potential to be developed in the Madura area. The main purpose of writing this scientific paper is to provide a normative description of the potential of the village sharia investment system as a supporting system for the creative economy in the Madura region. This study uses a qualitative descriptive method to provide an overview of the object of research. The data used is secondary data with literature study techniques as a data collection tool. The result of this research is a village sharia investment system platform that has the potential to be developed in the Madura area and can be an economic booster. The conclusion obtained is that the concept of the village sharia investment system is able to encourage the economy of East Java by developing Madura as a potential economic area through a creative economy based on village sharia investment system financing.